2013
DOI: 10.1093/ndt/gft429
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia in children on renal replacement therapy

Abstract: Dyslipidaemia is common among paediatric ESRD patients in Europe. Young age and PD treatment are associated with worse lipid profiles. Although lipid levels generally improve after transplantation, dyslipidaemia may persist due to decreased graft function, high BMI or to the use of certain immunosuppressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
3
13
2
1
Order By: Relevance
“…This is in accordance with the observations in adults showing an independent association of hypertriglyceridaemia with impaired renal allograft function beyond the first post-transplant year in multivariate analyses [40]. In a very recent register study, an inverse association between triglyceride levels and estimated GFR was similarly found in paediatric RTx patients [41]. Total cholesterol, HDL, or LDL did not have a comprehensive association with graft function in our patients ( Fig.…”
Section: Variablessupporting
confidence: 93%
“…This is in accordance with the observations in adults showing an independent association of hypertriglyceridaemia with impaired renal allograft function beyond the first post-transplant year in multivariate analyses [40]. In a very recent register study, an inverse association between triglyceride levels and estimated GFR was similarly found in paediatric RTx patients [41]. Total cholesterol, HDL, or LDL did not have a comprehensive association with graft function in our patients ( Fig.…”
Section: Variablessupporting
confidence: 93%
“…The prevalence of dyslipidemia was 88% at 1 year post‐transplant. This rate is higher than in previous studies which observed a broad range of 15%‐67% dyslipidemia in this patient population . However, definitions of dyslipidemia and applied reference values differed from study to study.…”
Section: Discussioncontrasting
confidence: 71%
“…Eventually, in children, prevalence data, reference values as well as treatment recommendations vary depending on country, study, and guideline . We therefore aimed to evaluate the prevalence of dyslipidemia in pediatric renal transplant recipients in a large international multicenter registry, and to identify possible non‐modifiable and modifiable risk factors including the most frequently used immunosuppressive regimens.…”
Section: Introductionmentioning
confidence: 99%
“…The baseline incidence of dyslipidaemia (without mTOR-I use) was estimated by Bonthuis et al 213 based on European registry data for child/adolescent RRT recipients. The incidence of dyslipidaemia was 55.5% (313/564) for transplant recipients, versus 85.1% and 76.1% for haemodialysis and peritoneal dialysis recipients, respectively.…”
Section: Dyslipidaemiamentioning
confidence: 99%